SICKLE CELL TRAIT, CLINICAL MANIFESTATIONS AND OUTCOMES: A CROSS-SECTIONAL STUDY - Diego A Vargas-Hernández; Adriana Catalina Uscategui-Ruiz; Andrés Jesus Prada-Rueda; Consuelo Romero-Sánchez (Mediterranean Journal of Hematology and Infectious Diseases)
Introduction: Sickle cell trait (SCT) is an autosomal recessive blood disorder in which patients are heterozygous carriers for hemoglobin S (HbAS) and are usually asymptomatic. We performed a descriptive analysis of clinical manifestations and outcomes associated with SCT.